Structural properties of fracture haematoma: current status and future clinical implications. (12th July 2016) - Wang, Xin; Friis, Thor; Glatt, Vaida; Crawford, Ross; Xiao, Yin
Abstract: Blood clots (haematomas) that form immediately following a bone fracture have been shown to be vital for the subsequent healing process. During the clotting process, a number of factors can influence the fibrin clot structure, such as fibrin polymerization, growth factor binding, cellular infiltration (including platelet retraction), protein concentrations and cytokines. The modulation of the fibrin clot structure within the fracture site has important clinical implications and could result in the development of multifunctional scaffolds that mimic the natural structure of a haematoma. Artificial haematoma structures such as these can be created from the patient's own blood and can therefore act as an ideal bone defect filling material for potential clinical application to accelerate bone regeneration. Copyright © 2016 John Wiley & Sons, Ltd.